The essential guide to freelance writing how to write, work, & thrive on your own terms - Petit, Zachary (Cincinnati, Ohio Writer's Digest Books, 2015)
"So you want to be a freelance writer. Great! But now you're faced with a laundry list of questions: Should I freelance full time or part time? Should I write for magazines, newspapers, or online markets? How do I dream up the perfect article idea, and how do I pitch it successfully? How do I negotiate contracts, foster relationships with editors, and start getting steady work while avoiding financial panic attacks and unpleasant ulcers? The Essential Guide to Freelance Writing won't just show you how to survive your freelancing writing career--it will teach you how to truly thrive" -- provided by publisher.
By way of introduction -- Battling, and besting, the basics -- Ideation vacation -- The dreaded platform discussion -- Finding a way in -- Pitch perfect -- Talking the talk -- Walking the walk -- The men and women behind the curtain -- Mostly not boring business basics -- 30 -- Appendix: the best stuff that wouldn't fit in the book proper.
Prof. Ma. Theresa Tabada (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Freelance journalism -- Handbooks, manuals, etc; Authorship